Towards the Sustainability of Food MSMEs through Strengthened Collaboration and Competitiveness - Sandi Setiadi; Alhidayatullah Alhidayatullah; Rizky Maulana (Lafadz Jaya Publisher, 2025)
The sustainability of Micro, Small, and Medium Enterprises (MSMEs) is the most pressing issue in economic, social, and environmental development in the modern era, where the focus of business has shifted from mere financial growth to social responsibility and resource sustainability. MSMEs, especially in the food sector in Sukabumi Regency, play a crucial role, although many still face challenges in terms of using modern technology and building extensive networks. This study aims to fill the gap by explicitly exploring the relationship between collaboration and competitiveness on the sustainability of MSMEs in the food sector, particularly in Sukabumi Regency, by considering these two variables in parallel.This study uses a descriptive quantitative method, taking a sample of 200 business actors from the total population of the food industry in Sukabumi Regency (3,501) through non-probability purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that the proposed model had very strong predictive power, as evidenced by an R-Square value of 0.963 and a Q² value of 0.632, confirming its high predictive relevance. Specifically, MSME collaboration was found to have a positive and significant effect on business sustainability (Original Sample 0.466). Collaboration enables business actors to share resources, information, and networks, which strengthens their capacity for adaptation and innovation. In addition, MSME competitiveness also has a positive and significant effect on business sustainability (Original Sample 0.519), which is achieved through operational efficiency and product differentiation. The synergy between collaboration and competitiveness is crucial to realizing resilient and competitive food MSMEs in Sukabumi.